Clinical Utility of GlioSeq Next-Generation Sequencing Test in Pediatric and Young Adult Patients With Brain Tumors. Issue 8 (10th June 2019) - Roy, Somak; Agnihotri, Sameer; El Hallani, Soufiane; Ernst, Wayne L; Wald, Abigail I; Santana dos Santos, Lucas; Hamilton, Ronald L; Horbinski, Craig M; Wadhwani, Nitin R; Born, Donald E; Pollack, Ian F; Nikiforov, Yuri E; et al.
Abstract: Brain tumors are the leading cause of death in children. Establishing an accurate diagnosis and therapy is critical for patient management. This study evaluated the clinical utility of GlioSeq, a next-generation sequencing (NGS) assay, for the diagnosis and management of pediatric and young adult patients with brain tumors. Between May 2015 and March 2017, 142 consecutive brain tumors were tested using GlioSeq v1 and subset using GlioSeq v2. Out of 142 samples, 63% were resection specimens and 37% were small stereotactic biopsies. GlioSeq sequencing was successful in 100% and 98.6% of the cases for the detection of mutations and copy number changes, and gene fusions, respectively. Average turnaround time was 8.7 days. Clinically significant genetic alterations were detected in 95%, 66.6%, and 66.1% of high-grade gliomas, medulloblastomas, and low-grade gliomas, respectively. GlioSeq enabled molecular-based stratification in 92 (65%) cases by specific molecular subtype assignment (70, 76.1%), substantiating a neuropathologic diagnosis (18, 19.6%), and diagnostic recategorization (4, 4.3%). Fifty-seven percent of the cases harbored therapeutically actionable findings. GlioSeq NGS analysis offers rapid detection of a wide range of genetic alterations across a spectrum of pediatric brain tumors using formalin-fixed, paraffin-embedded specimens and facilitates integrated molecular-morphologic classification and personalized management of pediatric brain tumors.